Potentials of musyarakah as a financing mechanism for SMES in Malaysia - Nur Hasnida binti Abd. Rahman (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2017)
Small and medium enterprise (SMEs) has been recognised as an important component that contributes towards the economic growth of many countries around the world. Despite its importance, SMEs have limited access to external financing, which is dominated by debt financing. They have difficulties in fulfilling debt requirements, particularly in (i) providing collateral (ii) coping with high interest or profit payment and (iii) adapting to credit rationing. Such limitations hamper their growth and expansion and therefore they are in need for an alternative financing that is more accessible by them. This study examines the viability of Musyarakah as an alternative financing for SMEs. For this purpose, three main features of Musyarakah financing, namely banks' participation in SMEs business operations, risk-sharing and profit and loss sharing were identified as potential instruments in assisting SMEs to have better access to financing. Moreover, three moderating factors, namely expertise, incentive-compatible contract and mutual trust, were identified to have potential in strengthening the effect of the main features of Musyarakah financing towards SMEs access to financing. A Musyarakah financing mechanism for SMEs is developed on the basis of these main features of Musyarakah and its moderating factors. Subsequently, the financing mechanism is further validated from both the supply and demand sides using a mixed-method approach. A quantitative method via a survey questionnaire was conducted on SMEs firms to validate the Musyarakah financing mechanism from the demand side. The results were analysed using structural equation modelling and the findings revealed that the Musyarakah financing mechanism is valid and has potential in providing SMEs with better access to financing. Concurrently, semi-structured interviews were conducted to obtain the bankers' views of the said mechanism. The result of these interviews, note that the mechanism is acceptable and has potential in assisting SMEs to have better access to financing. These findings from both the demand and supply side suggest that Musyarakah financing is a viable alternative for SMEs. Greater access to financing will facilitate SMEs' growth and development which in turn, contributes to the economic growth of the country. Thus, financial institutions are proposed to give foremost attention to the development and offering of Musyarakah financing for SMEs.